2014
DOI: 10.1111/nuf.12051
|View full text |Cite
|
Sign up to set email alerts
|

Access to Health Care by Refugees: A Dimensional Analysis

Abstract: Knowledge of this unique population is integral to healthcare professionals who encounter refugees in clinical practice. Regardless of the specific group, access to healthcare services must be determined for better health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
(51 reference statements)
1
19
1
Order By: Relevance
“…The women's commitment to regular attendance and willingness to tell their stories was powerful. Some of the barriers identified by Navuluri and colleagues (2014) and Szajna and Ward (2015) also emerged during the PW sessions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The women's commitment to regular attendance and willingness to tell their stories was powerful. Some of the barriers identified by Navuluri and colleagues (2014) and Szajna and Ward (2015) also emerged during the PW sessions.…”
Section: Resultsmentioning
confidence: 99%
“…In order to better serve this community, nurses must assess the barriers that refugees face. However, refugees are not a homogeneous group, and cultural norms, values, and beliefs vary creating health care delivery challenges (Szajna & Ward, 2015). Despite the dedication, care, and rigor invested in the development of culturally sensitive screening instruments, there is the risk of cultural bias when using ordinal scales as they may not translate effectively across cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study that focused on health care providers’ perspectives of refugees access to health care services [28], refugees experienced additional barriers in language and interpretation, differences in culture, health care coverage, availability of services, isolation, poverty, and poor transport. In a dimensional analysis of refugees access to health care, it was found that a sense of discrimination and stigmatization, and logistical concerns were additional barriers to refugees’ access to health care services [29]. Moreover, refugees fear accessing health care services where their immigration status can be questioned or reported to law enforcement authorities [11, 27, 28] and being denied care [21].…”
Section: Introductionmentioning
confidence: 99%
“…During the first eight months post resettlement to the US, all refugees qualify for federally funded Refugee Medical Assistance (RMA) and cash assistance (ORR, 2012b). Previous literature exploring health practices in refugee populations identify cost and lack of insurance as a significant barrier to healthcare utilization (Szajna & Ward, 2015); thus, it is important to focus on Bhutanese refugees after the initial resettlement benefits end. We excluded refugees living in the US for greater than five years since greater likelihood that familiarity with mainstream health practices in the US increases with time spent in the US.…”
Section: Sample and Settingmentioning
confidence: 99%